Estudo da bioquímica salivar de crianças e adolescentes com atresia de vias biliares pré e pós transplante hepático - Buosi, Debora Fernandes [UNIFESP] (2019)
Objective: This study aimed to evaluate some salivary parameters of children and adolescents with biliary atresia before and after liver transplantation. Methods: The sample consisted of 69 children and adolescents, both sexes, edentulous, deciduous, mixed and permanent dentures, attended at the Pediatric Gastroenterology and Liver Transplantation outpatient clinics of Unifesp. They were divided into three distinct groups: bile duct atresia group (AVB=29), hepatic post-transplant group (TxH=20) and without systemic diseases Control group (C=20). Saliva was collected by the non-stimulated aspiration method and the salivary amylase, sialic acid, total protein, calcium and phosphate concentration were analyzed and the readings were performed by the spectrophotometer. Results: Salivary amylase and sialic acid in the group (AVB) are significantly reduced in relation to the other groups. The total protein was elevated in the AVB group in relation to the TxH group. Calcium showed no difference between the AVB, TxH and C groups. Phosphate was decreased in patients with mixed dentition in the AVB and TxH groups. In patients with deciduous dentition the phosphate was higher in the AVB and TxH group when compared to the control group. Conclusion: Sialic acid and amylase in patients with AVB are reduced in relation to the other groups (TxH and control). The total protein in the AVB group is increased in relation to the TxH group. There was no difference between the groups regarding salivary calcium. Salivary phosphate presented alterations: higher in the AVB group in relation to the control. Decreased in patients with mixed dentition in AVB and TxH groups. In patients with deciduous dentition the phosphate was higher in the AVB and TxH group when compared to the control group.